Second-to-fourth digit length ratio as a measure of harm avoidance. (July 2016) - Jeon, Sang Won; Yoon, Ho-Kyoung; Han, Changsu; Ko, Young-Hoon; Kim, Yong-Ku; Won, You Joon
Abstract: Research on the associations between the ratio of second-to-fourth digit lengths (2D:4D ratio) and psychological variables could be a useful method of confirming sex hormone effects on human behavior tendencies. This study investigated the correlations between the 2D:4D ratio and characteristics of temperament and character in an urban community population. We hypothesized that the 2D:4D ratio correlates more strongly with temperament than with character. A total of 728 healthy adults (330 men and 398 women) ranging in age from 20 to 45 years were tested. Subjects completed the Temperament and Character Inventory (TCI) and were examined by measuring the 2D:4D ratio using a direct measurement method. Correlations between the 2D:4D ratio and psychological characteristics were explored. For women only, significant positive correlations with the 2D:4D ratio were found in the TCI-Temperament dimension (TCI-T), particularly in the two subscales of harm avoidance scale. Women with higher 2D:4D ratios had higher fear of uncertainly scores ( r partial  = 0.206, p  = 0.028) and shyness with strangers scores ( r partial  = 0.252, p  = 0.024). The 2D:4D ratio shows stronger correlations with temperament than with character. A higher 2D:4D ratio of woman is expected to indicate harm avoidance. Highlights: This study investigated the correlations between the 2D:4D ratio and characteristics of temperament and character. The 2D:4D ratio shows a stronger correlation with temperament than with character. A higher 2D:4D ratio with woman is expected to indicate harm avoidance.